Flexor carpi radialis H-reflex in different body positions in patients with post-stroke - Ma, Jia-Yin; Wu, Jia-Jia; Zheng, Mou-Xiong; Hua, Xu-Yun; Shan, Chun-Lei; Xu, Jian-Guang (Frontiers in Neurology, 2022)
Backgroud: Spinal stretch reflex (SSR) hyperexcitability reflected by the H-reflex has been reported in more strongly affected extremities after stroke. The H-reflex in lower extremities is modulated by body position normally and alternatively modulated post stroke. Objective: This study aimed to preliminarily explore how upper extremity (UE) H-reflexes are modulated by body position after stroke, which remains unknown. Materials and methods: Three patients after stroke with hemiparesis/hemiplegia were included. Bilateral flexor carpi radialis (FCR) H-reflexes were examined in the supine position and while standing. Other clinical evaluations including the modified Ashworth scale (MAS) and postural stability measurement. Results: The three cases herein showed that (1) SSR excitability was higher in more strongly affected UEs than less-affected UEs; (2) down-modulation of SSR excitability occurred in less-affected UEs in static standing compared to the supine position, but modulation of SSR excitability in more-affected UEs varied; and (3) bilateral UE SSR excitability in case 3 was down-modulated the most. Moreover, case 3 showed no difference in muscle tone of the more affected UE between supine and standing positions, and case 3 showed the best postural stability. Conclusion: SSR hyperexcitability in strongly affected UEs could commonly occur in different phases of recovery after stroke. Down-modulation of SSR excitability could occur in less-affected UEs in the standing position compared to the supine position, while modulation of SSR excitability might be altered in strongly affected UEs and vary in different phases of recovery. There could be some correlation between postural control and UE SSR hyperexcitability. The H-reflex may help to offer a new perspective on rehabilitation evaluation and interventions to promoting UE motor control after stroke.